Circular RNA circCUL3 Accelerates the Warburg Effect Progression of Gastric Cancer through Regulating the STAT3/HK2 Axis - Zhichen Pu; Maodi Xu; Xiaolong Yuan; Haitang Xie; Jun Zhao (Elsevier, 2020)
The Warburg effect is a significant hallmark of gastric cancer (GC), and increasing evidence emphasizes the crucial role of circular RNAs (circRNAs) in GC tumorigenesis. However, the precise molecular mechanisms by which circRNAs drive the GC Warburg effect are still elusive. The present study was designed to unveil the roles of circRNAs and the corresponding potential mechanism. High-regulated expression of circCUL3 was observed in both GC tissues and cell lines. Clinically, the high expression of circCUL3 was closely correlated with advanced clinical stage and overall survival in GC patients. Functionally, cellular experimental investigations demonstrated that circCUL3 promoted the proliferation, glucose consumption, lactate production, ATP quantity, and extracellular acidification rate (ECAR) of GC cells. In vivo, circCUL3 knockdown repressed tumor growth. Mechanistic analysis demonstrated that circCUL3 promoted signal transducer and activator of transcription (STAT)3 expression through sponging miR-515-5p; moreover, transcription factor STAT3 accelerated the transcriptional level of hexokinase 2 (HK2). In summary, the present findings provide mechanistic insights into circCUL3/miR-515-5p/STAT3/HK2 axis regulation on the GC Warburg effect, providing a novel possibility for an understanding of GC pathogenesis.